Convection boundary layer flow over various surfaces in nanofluid - Omar, Noor Syamimi (2016)
The study of convection boundary layer ows over various surfaces in nano u- ids is considered. Conventional heat transfer uids, such as water, ethylene glycol and engine oil, have limited capabilities, hence, limiting the enhance- ment of the performance of the thermal applications. On the other hand, most solids, such as metals, oxides, carbides or carbon nanotubes, have unique phys- ical properties (nano-sized particles and high thermal conductivity). Thus, an innovative idea has been introduced, which, uses a mixture of nanoparticles and base uid in order to develop advanced heat transfer uids with substan- tially higher conductivities. In this study, mathematical models are derived for three different problems of boundary layer ow and heat transfer over a moving plate, stretching or shrinking cylinder and stretching or shrinking sheet in nano uids. The governing nonlinear partial differential equations are transformed into a system of nonlinear ordinary differential equations using a similarity transformation. The resulting system of equation are solved numer- ically for three diffrent nanoparticles, namely copper (Cu), alumina (Al2O3) and titania (TiO2) in a water-based uid with Prandtl number (Pr = 6.2) by using shooting technique with MAPLE software. The numerical results are presented in tables and graphs for the skin friction coeficient, the local Nusselt number and the local Sherwood number as well as the velocity, tem- perature and concentration profiles for a range of various parameters such as nanoparticles volume fraction, ', velocity ratio parameter, stretching or shrinking parameter, ", curvature parameter, , stratification parameter, St, magnetic field paramter, M, and suction parameter, s. It is observed that the skin friction coeficient, the local Nusselt number which represents the heat transfer rate at the surface and the local Sherwood number are signifi-cantly in uenced by these parameters. Moreover, dual and unique solutions are obtained for a certain range of the parameters involved and inclusion of nanoparticles in water-base uid does affects the skin friction coeficient as well as the heat transfer rate.